Development and Validation of the Values Internalization Scale - Lanting Wu; Youguo Chen; Xiting Huang (Behavioral Sciences)
Clarifying the stages of the values internalization process enables a more effective selection of interventions to promote targeted internalization. However, no specialized instrument currently exists to measure this process. Grounded in the four-stage model of values internalization, this study aimed to develop and validate a Values Internalization Scale (VIS) for adults. Data from Sample 1 (N = 474) were subjected to item analysis and exploratory factor analysis, yielding a scale with a four-factor structure. Subsequently, confirmatory factor analysis and reliability and validity tests were conducted using Sample 2 (N = 470). The results indicated that the four-factor model demonstrated a good model fit and that the scale exhibited satisfactory internal consistency reliability, criterion-related validity, and test–retest reliability. The final 25-item VIS comprises four dimensions: ignoring-resistance, understanding, attempt to practice, and integration stages. The 25-item VIS developed in this study performed exceptionally well regarding reliability and validity and can be utilized in subsequent research on the internalization of values.